Методика вивчення тригонометричних рівнянь і нерівностей у загальноосвітній школі - Юр’єва, Поліна Борисівна; Yurieva, Polina Borysivna (Ірпінь, 2024)
Тригонометричні рівняння і нерівності широко представлені у завданнях державної підсумкової атестації та в завданнях зовнішнього незалежного оцінювання з математики. Як засвідчують аналітичні звіти Українського центру оцінювання якості освіти, результати виконання цих завдань в останні роки суттєво погіршилися, що вимагає пошуку шляхів удосконалення методики вивчення рівнянь та нерівностей, зокрема тригонометричних. Це робить актуальною проблему вдосконалення методики навчання учнів розв’язуванню рівнянь та нерівностей з позицій компетентнісного підходу.

Trigonometric equations and inequalities are widely represented in tasks of state final certification and tasks of external independent assessment in mathematics. As evidenced by the analytical reports of the Ukrainian Center for the Evaluation of the Quality of Education, the results of these tasks have significantly deteriorated in recent years, which requires finding ways to improve the methodology of studying equations and inequalities, in particular trigonometric ones. This makes the problem of improving the methodology of teaching students to solve equations and inequalities from the standpoint of the competence approach urgent.
Methods of studying trigonometric equations and inequalities in secondary school
Keywords: методика навчання математики; тригонометричні рівняння і нерівності; mathematics teaching methods; trigonometric equations and inequalities